EFFECTIVENESS OF AGRICULTURAL DEVELOPMENT PROGRAMME COMMUNICATION METHODS ON BROILER PRODUCTION TECHNOLOGY ADOPTION AMONG FARMERS IN ANAMBRA STATE, NIGERIA - Eucharia Ogochukwu CHUKWUDUM (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Pines stands from outside their areal were created from 1972 in field and plain areas with the purpose of substituting degraded stands (oaks) or derived ones (linden, hornbeam). These cultures had a good evolution up to the age of 30-35 years, after which they were affected by drought and/or breaks with an effect on their stability, protection, regeneration functions and forest continuity. The degree of damaged caused and the danger that this phenomenon poses in disordering the ecologic equilibrium requires the adoption and appliance of complex silvotechnical measures and works. The present paper shortly presents data regarding the current state of pine stands situated outside their areal as well as their ecological reconstruction solutions. These solutions were scientifically sustained based on the results of investigations realized during 2015-2018. The ecological reconstruction works of pine stands located outside their areal are necessary for improving their current structure, as well as their capacity for ensuring regeneration and their transition towards other forest zonal types. The recommended ecological reconstruction solutions intend to reestablish a natural forest type by substituting pine stands from lands located in “natural” stations or slightly altered towards a natural forest type. This can be achieved by restoring-substituting pine stands situated in moderately degraded lands with improved vegetation conditions.